Pharmacokinetics of Quinupristin-Dalfopristin in Continuous Ambulatory Peritoneal Dialysis Patients - Johnson, Curtis A. (American Society for Microbiology, 1999)
Quinupristin-dalfopristin may be useful for treatment of organisms causing peritoneal dialysis-related peritonitis, including methicillin-resistant coagulase-negative staphylococci, methicillin-resistant Staphylococcus aureus, and vancomycin-resistant enterococci. The pharmacokinetic profiles of single intravenous doses of this combination streptogramin antibiotic of 7.5 mg/kg of body weight were characterized for eight noninfected patients receiving continuous ambulatory peritoneal dialysis. Comparison was made to pharmacokinetic profiles determined for eight healthy volunteers matched by age, sex, and race. Drug was measured in dialysate up to 6 h following the dose. Plasma and dialysate were assayed for parent compounds and metabolites. Mean pharmacokinetic parameters were compared between groups. No statistically significant differences were observed between groups for maximal concentrations in plasma, times to maximal concentration, areas under the curve, distribution volumes, rates of total body clearance, or half-lives in plasma for quinupristin and dalfopristin. No statistically significant differences were observed in maximal concentrations in plasma, times to maximal concentration, areas under the curve, or half-lives for cysteine, the glutathione conjugates of quinupristin, or the pristinamycin IIA metabolite of dalfopristin. The measurements in dialysate of the parent and most metabolites were below the expected MICs. Dialysis clearance was insignificant. Quinupristin-dalfopristin was well tolerated in both groups, causing only mild adverse events that resolved prior to discharge from the study. The disposition of quinupristin, dalfopristin, or their primary metabolites following a single dose was unaltered in patients receiving peritoneal dialysis. Intravenous dosing of this antibiotic combination is unlikely to be adequate for the treatment of peritonitis associated with peritoneal dialysis.